Locked out: felon disenfranchisement and American democracy - Manza, Jeff (Studies in crime and public policy, 2006)
Exposes felon disenfranchisement as one of the most important, yet little known, threats to the health of American democracy. This book reveals the centrality of racial factors in the origins of these laws, and their impact on politics, election outcomes, and public policy